2014
DOI: 10.1159/000362236
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Tolerability of a High Loading Dose (25,000 IU Weekly) Vitamin D<sub>3</sub> Supplementation in Obese Children with Vitamin D Insufficiency/Deficiency

Abstract: Background: The recommended dose of vitamin D supplementation of 400 IU/day might be inadequate to treat obese children with vitamin D insufficiency. Therefore, we tested the efficacy and tolerability of a high loading dose vitamin D3 supplementation of 25,000 IU weekly in multiethnic obese children, 8-18 years of age, with vitamin D insufficiency/deficiency. Methods: Fasting blood samples were drawn for the assessment of vitamin D. Vitamin D-insufficient/-deficient children (<50 nmol/l) were supple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
1
4
0
1
Order By: Relevance
“…Prior to our study, there was no consensus on the recommended dose of vitamin D to achieve sufficiency in children and adolescents with overweight/obesity, nor whether the high doses of vitamin D that may be required to achieve an ideal 25(OH)D level would do so at the cost of toxicity. Previous studies in children and adolescents with overweight/obesity have demonstrated that higher loading doses of oral vitamin D may be indicated in children and adolescents with higher body fat given their lower rise in serum vitamin D levels compared with children and adolescents with a normal BMI, consistent with our PK analysis in this study showing that doses much higher than standard of care are needed for children and adolescents with overweight/obesity and asthma 19,20 . The prevalence of vitamin D deficiency in children with overweight/obesity in the United States varies based on geographic location, time of year, skin color, and the definition of vitamin D deficiency utilized 18 .…”
Section: Discussionsupporting
confidence: 87%
“…Prior to our study, there was no consensus on the recommended dose of vitamin D to achieve sufficiency in children and adolescents with overweight/obesity, nor whether the high doses of vitamin D that may be required to achieve an ideal 25(OH)D level would do so at the cost of toxicity. Previous studies in children and adolescents with overweight/obesity have demonstrated that higher loading doses of oral vitamin D may be indicated in children and adolescents with higher body fat given their lower rise in serum vitamin D levels compared with children and adolescents with a normal BMI, consistent with our PK analysis in this study showing that doses much higher than standard of care are needed for children and adolescents with overweight/obesity and asthma 19,20 . The prevalence of vitamin D deficiency in children with overweight/obesity in the United States varies based on geographic location, time of year, skin color, and the definition of vitamin D deficiency utilized 18 .…”
Section: Discussionsupporting
confidence: 87%
“…The current evidence does not support vitamin D supplementation as monotherapy for children with ASD. However, it seems feasible that vitamin D might be used to complement other treatments for ASD considering its long-term tolerability and acceptability 42,43 , its critical role in brain function and development, and its roles in various metabolic pathways involved in the pathobiology of ASD 38 . It will be important to employ one uniform assessment tool in order to reduce methodological bias.…”
Section: Discussionmentioning
confidence: 99%
“…Recommendation of Endocrine Society guidelines suggested with 50,000 IU once a week for 8 weeks or 6000 IU/ day of vitamin D3 to achieve a serum concentration of 25 (OH)D3 > 30 ng/mL, followed by maintenance therapy of 1500-2000 IU/day [44]. A vitamin D supplementation with 25,000 IU weekly in young people with obesity (8-18-year olds) was found to be well tolerated and restored a sufficient vitamin D status in more than 84% of individuals [116].…”
Section: Vitamin D Treatmentmentioning
confidence: 97%